Hanseniaspora vineae and the Concept of Friendly Yeasts to Increase Autochthonous Wine Flavor Diversity - Carrau, Francisco; Henschke, Paul A. (Frontiers in Microbiology, 2021)
We will explain the concept of ‘friendly’ yeasts for developing wine starters that do not suppress desirable native microbial flora at the initial steps of fermentation, as usually happen with Saccharomyces strains. Some non-Saccharomyces strains might allow the development of a yeast consortia with the native terroir microflora of the grapes and its region. The positive contribution of non-Saccharomyces yeasts was underestimated for decades. Avoiding them as spoilage strains and off-flavors producers was the main objective in winemaking. It is understandable, as in our experience after more than thirty years of wine yeasts selection, it was shown that no more than 10% of the native isolated strains were positive contributors of superior flavors. Hanseniaspora vineae systematically gave desirable flavors during these screening processes. H. vineae is an active fermentative species, and this fact help to build an improved juice ecosystem, avoiding contaminations of aerobic bacteria and yeasts. Why H. vineae shares the fermentation niche with other yeast strains? It might be due to the friendly conditions it creates, such as ideal low temperatures and low nitrogen demand during fermentation, reduce synthesis of medium chain fatty acids and a rich acetylation capacity of aromatic higher alcohols, well-known inhibitors of many yeasts. We will discuss here that inoculation of H. vineae strains can give the winemaker an opportunity to develop the ideal conditions for flavor expression of the microbial terroir without the risk of undesirable strains that can result from spontaneous fermentations.